Incarceration and Support for Children in Fragile Families - Amanda Geller
Incarceration is widespread in the United States, and previous literature has shown significant negative effects of incarceration on later employment, earnings, and relationship stability. Given the high rates of fatherhood among men in jails and prisons, a large number of children are placed at considerable risk when a parent is incarcerated. This paper examines one dimension of the economic risk faced by children of incarcerated fathers: the reduction in the financial support that they receive. We use a population-based sample of urban children to examine the effects of incarceration on this support. Both cross-sectional and longitudinal regression models, as well as a propensity score matching analysis, indicate that men with incarceration histories are significantly less likely to contribute to their families and those that do contribute provide significantly less. Moreover, sensitivity analysis suggests that these differences are unlikely to be a result of unobserved heterogeneity between incarcerated and never-incarcerated fathers. The negative effects of incarceration on fathers’ financial support are due not only to diminished performance in the labor market by formerly incarcerated men, but also to their increased likelihood to live apart from their children. Men contribute far less through child support (formal or informal) than they do when they share their earnings within their household, suggesting that the destabilizing effects of incarceration on family relationships place children at significant economic disadvantage.